PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN BERBICARA DAN KEPERCAYAAN DIRI SISWA KELAS 4 SDN 6 KESIMAN - Ni Putu Sudiarti; Ni Wayan Serra Yuni Ari Cahyani; Ni Nyoman Sri Arianti; Luh Putu Cakrawati; I Nyoman Sudiana; Ida Bagus Putrayasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays a crucial role in shaping students' character and skills. One of the essential skills needed in daily life is speaking ability. Good speaking skills are not only important in education but also in communication within society. However, many students lack the confidence to speak in front of the class, which hinders the development of their speaking skills. Therefore, a learning model that can improve both speaking skills and students' self-confidence is needed. This study aims to examine the effect of the cooperative learning model Think Pair Share (TPS) on the speaking ability and self-confidence of fourth-grade students at SDN 6 Kesiman. This research employed an experimental method with a quantitative approach and a pretest-posttest control group design. The subjects of the study consisted of two classes: an experimental class that implemented the TPS model and a control class that used a conventional learning model. Data were collected through speaking ability tests, observations, and interviews, and analyzed using statistical tests to examine the differences between the experimental and control classes. The results showed a significant improvement in students' speaking abilities in the experimental class after the implementation of the TPS model. The average post- test score of students' speaking ability in the experimental class increased significantly from 62.00 to 82.33, while the control class only showed an increase from 61.53 to 69.30. The hypothesis test results indicated that this difference was significant with a significance value of 0.000 < 0.05. In addition, the TPS model also proved effective in enhancing students' self-confidence. Students who were previously hesitant and passive began to show the courage to speak and express their opinions in front of their peers. This increase in self-confidence was further supported by the results of the normalized gain test, which showed higher scores in the experimental class compared to the control class. Based on these findings, it can be concluded that the application of the Think Pair Share (TPS) cooperative learning model has a positive impact on improving students' speaking skills and self- confidence.